(untitled) (The Journal of Forensic Accounting Profession, 2021)
The field of business ethics has received considerable attention from the corporate, academic, and public sectors over the past several decades. A key purpose of this paper is to examine existing research and knowledge creation in the field of business ethics. The paper includes systematic literature review using bibliomteric analysis which covers 50 articles, published in 11 peer-reviewed journals from 1994 to 2019, examining the methodological and theoretical approaches, as well as the main research focus areas. We found significant amount of studies concerning business ethics appeared mostly in business ethics journals. We identified seven areas of research covered by numerous authors in the observed period, of which three predominate: corporate culture; education; and national (cultural) approach to business ethics. (Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2021-0001, pod licencom CC BY-NC-ND 4.0)